Neutron scattering applications in biology, chemistry, and materials science - Fernandez-Alonso, Felix; Price, David L. 1940- (Academic Press is an imprint of Elsevier, 2017)
"Neutron Scattering: Applications in Chemistry, Materials Science and Biology, Volume 49, provides an in-depth overview of the applications of neutron scattering in the fields of physics, materials science, chemistry, biology, the earth sciences, and engineering. The book describes the tremendous advances in instrumental, experimental, and computational techniques over the past quarter-century. Examples include the coming-of-age of neutron reflectivity and spin-echo spectroscopy, the advent of brighter accelerator-based neutron facilities and associated techniques in the United States and Japan over the past decade, and current efforts in Europe to develop long-pulse, ultra-intense spallation neutron sources. It acts as a complement to two earlier volumes in the Experimental Methods in the Physical Science series, Neutron Scattering: Fundamentals(Elsevier 2013) and Neutron Scattering: Magnetic and Quantum Phenomena (Elsevier 2015). As a whole, the set enables researchers to identify aspects of their work where neutron scattering techniques might contribute, conceive the important experiments to be done, assess what is required, write a successful proposal for one of the major facilities around the globe, and perform the experiments under the guidance of the appropriate instrument scientist." -- From the publisher
Includes index
Includes bibliographical references and index
Keywords: SCIENCE / Physics / Quantum Theory; Neutrons / Scattering; Neutrons -- Scattering; Chemie; Werkstoffkunde; Biologie; Neutronenstreuung